Geology, petrography e geochemistry of the TTG associations and leucogranodiorites of the extreme north of Rio Maria Domain, Carajás Province - Ronaib, Chrystophe (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses